Partitioning into training and testing sets. - Chunliang Jiang (22477803) (2025)
Objectives Accurately predicting the mortality risk of hypothermia patients is crucial for clinical decision-making, offering ample time for physicians to intervene. However, existing methods are invasive and difficult to implement in pre-hospital settings. Methods In this study, records of 2,700 hypothermia patients from 125 hospitals were extracted from the eICU Collaborative Research database, comprising 360 non-survivors and 2,340 survivors. Four machine learning methods were utilized to develop a mortality prediction model for hypothermia patients based on non-invasive physiological parameters. Data from 122 hospitals were used for model training, while the remainder were utilized for performance validation. Results The proposed machine learning prediction model achieved an area under the receiver operating characteristic curve (AUC) of 0.869 (95%CI: 0.840–0.895), demonstrating good mortality predictive performance for hypothermia patients only using non-invasive physiological parameters. Optimal and minimal feature subsets were selected for each machine learning method. The optimal feature subsets contained only 70.6% of the overall features for XGBoost models, while the AUC values increased by 0.039 compared to that of the entire feature subset. The interpretability analysis results highlight the vital importance of the temperature feature in predicting mortality during episodes of hypothermia in patients. Conclusions This study developed a mortality prediction method for hypothermia patients only using non-invasive parameters, demonstrating robustness and reliability during multi-center validation. It can offer decision support for remote areas and disaster sites where it is difficult to access invasive parameters.